Exploring the relationship between GDP, carbon dioxide emissions, energy consumption, population, and renewable energy production using Canada as a model country - Chew, Jia Ming; Yap, Chee Kong; Krishnan Kumar; Cheng, Wan Hee; Wan Mohd Syazwan; Rosimah Nulit; Noor Azrizal-Wahid; Muskhazli Mustafa; Hideo Okamura; Yoshifumi Horie; Yap, Chee Wah; Kennedy Aaron Aguol; et al. (Universal Wiser publisher, 2024)
This study explores the complex relationships between population growth, gross domestic productivity (GDP), carbon dioxide (CO2) emissions, primary energy consumption, and renewable energy (RE) production in Canada from 1950 to 2021. Using time-series econometric techniques, including Ordinary Least Squares (OLS), Vector Autoregressive (VAR) models, and cointegration analysis, the research investigates how these variables interact over time and their implications for environmental sustainability and economic development. The results indicate that population and GDP growth significantly increase primary energy consumption and CO2 emissions, emphasizing the need for cleaner energy sources. While the positive correlation between population growth and renewable energy production presents opportunities for reducing carbon footprints and fostering economic resilience, there are also risks of overexploitation of renewable resources if energy demand outpaces sustainable supply. The study highlights the importance of sustainable resource management and policy frameworks to ensure that economic growth does not compromise environmental integrity. These findings provide critical insights for policymakers in balancing economic development with environmental sustainability, advocating for increased investment in renewable energy and implementing energy-efficient practices. Future research should expand this analysis to other countries and explore the differentiated impact of various renewable energy sources on economic and environmental outcomes.